A trinuclear Cu(II) precursor for solvatochromically distinguishing CH3OH from C2H5OH. Issue 22 (17th December 2019) - Gao, Xue-Mei; Ma, Wen; Jin, Gang; Li, Jing-Zhe; Wei, Xue-Wen; Liu, Kuan-Guan
Abstract: In order to develop an easy and rapid identification method for distinguishing CH3 OH from C2 H5 OH, a new carbonate-based trinuclear Cu(II) precursor, [Cu3 (bpy)6 (μ3 -CO3 )(CH3 OH)](BF4 )4 ·(CH3 OH)2 ·(H2 O)2 (1 ), has been isolated. We report here the synthesis, crystal structure, and characterizations by various spectroscopic (IR, UV–Vis, powder XRD) techniques, as well as the solvatochromic behavior of this coordination compound. Its X-ray crystal structure reveals that the main structure of 1 consists of three [(bpy)2 Cu] 2+ centers, which are bridged by carbonate via a μ3 -η 1, η 1, η 1 fashion. Strong O–H⋯O hydrogen bonding between the carbonate and solvent molecules has been observed for the first time in similar structures. Its ground powder exhibits solvatochromic behavior that selectively distinguishes CH3 OH from C2 H5 OH. Graphical Abstract: